Effect of Physician-Staffed Emergency Medical Services (P-EMS) on the Outcome of Patients with Severe Traumatic Brain Injury: A Review of the Literature. (3rd September 2019) - Popal, Zar; Bossers, Sebastiaan M.; Terra, Maartje; Schober, Patrick; de Leeuw, Marcel A.; Bloemers, Frank W.; Giannakopoulos, Georgios F.
Abstract: Introduction: Traumatic injury is the fourth leading cause of death in western countries and the leading cause of death in younger age. However, it is still unclear which groups of patients benefit most from advanced prehospital trauma care. A minimal amount is known about the effect of prehospital physician-based care on patients with specifically traumatic brain injury (TBI). The aim of this review is to assess the effect of physician-staffed Emergency Medical Services (EMS) on the outcome of patients with severe TBI. Methods: Literature searches have been performed in the bibliographic databases of PubMed, EMBASE and The Cochrane Library. Data concerning (physician-staffed) prehospital care for patients with severe TBI were only included if the control group was based on non-physician-staffed EMS. Primarily the mortality rate and secondarily the neurological outcome were examined. Additionally, data concerning hypotension, hypoxia, length of stay (hospital and intensive care unit) and the number of required early neurosurgical interventions were taken into account. Results: The overall mortality was decreased in three of the fourteen included studies after the implementation of a physician in the prehospital setting. One study found also a decrease in mortality only for patients with a Glasgow Coma Scale of 6–8. Strikingly, two other studies reported higher mortality, one for all the included patients and one for patients with GCS 10–12 only. Neurological outcome was improved in five studies after prehospital deployment of a physician. One study reported that more patients had a poor neurological outcome in the P-EMS group. Results of the remaining outcome measures differed widely. Conclusion: The included literature did not show a clear beneficial effect of P-EMS in the prehospital management of patients with severe TBI. The available evidence showed contradictory results, suggesting more research should be performed in this field with focus on decreasing heterogeneity in the compared groups.